Ectopia Cordis Associated with Pentalogy of Cantrell-A Case Report - José Mauro Madi; José Roberto Festugatto; Matheus Rizzon; Ana Paula Agostini; Breno Fauth de Araújo; Rosa Maria Rahmi Garcia (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Pentalogy of Cantrell (PC) is a rare congenital anomaly characterized by changes in the mesodermal median structures and congenital heart disease, often with a poor prognosis. In 1958, Cantrell et al2 defined the full spectrum of the syndrome with the following anomalies: defects of the anterior diaphragm, of the lower part of the sternum, of the supraumbilical region and the abdominal wall, of the diaphragmatic pericardium, and various intracardiac congenital abnormalities. The present report describes a case of ectopia cordis associated with PC and the importance of the participation of a multidisciplinary team in the treatment of this condition.